Structural Relationship of Metacognitive Beliefs, Stress, Attachment Styles with Anorexia Nervosa Mediated by Self-Image - Kashani Vahid, Sara; Mohammadi Aria, Alireza; Abolmaali Alhosseini, Khadijeh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The aim of this study was to determine the structural relationship between metacognitive beliefs, stress, attachment styles, and anorexia nervosa mediated by self-image.Methods: This research is a descriptive correlational study and is a type of modeling research; the study population included female middle school students from Tehran in the 2022-2023 academic year. The research sample was collected through convenience sampling. Participants included 215 female students who completed online questionnaires on Anorexia Nervosa (Stice et al., 2004), Body Self-Image (Rue & Associates, 1999), Anxiety, Depression, Stress-21 (Lovibond & Lovibond, 1995), Metacognitive Beliefs-30 (Cartwright et al., 2004), and the Adult Attachment Styles Questionnaire (Besharat, 2005). Data were analyzed using the Partial Least Squares method in SPSS and Smart-PLS software.Findings: The results showed that the modified structural relationship model of metacognitive beliefs, stress, and attachment styles with anorexia nervosa mediated by body self-image had the necessary fit.Conclusion: Based on the results obtained, it can be concluded that body self-image played a mediating role in the relationship between metacognitive beliefs, stress, and attachment styles with anorexia nervosa.